Exploring Barriers, Facilitators, and Needs Related to Mental Health Promotion for Police Officers: A Qualitative Approach - Gi Wook Ryu PhD, RN; Ji Yeon Lee PhD, RN, GNP-BC (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Police officers are vulnerable to psychological distress and trauma since they are constantly exposed to significant physical and mental violence. Poor mental health can lead to increased healthcare costs for individuals, organizations, and nations and negatively impacts public safety. Mental health interventions tailored to the nature of police work are needed; however, a research gap exists regarding understanding the mental health of police officers. This study aimed to explore the barriers, facilitators, and needs for mental health promotion among police officers. This study adopted a qualitative approach in South Korea. Twelve police officers working in a metropolitan city were recruited using purposive sampling methods. One-on-one interviews were conducted with open-ended questions regarding barriers, facilitators, and needs for improving mental health. Content analysis was used to derive relevant themes. The participants included 3 women and 9 men, with an average age of 37.8 years and working experience of 12.6 years. Three themes and 9 subcategories emerged. The theme related to barriers was “difficulty accessing resources”; the theme related to facilitators was “supportive environment for mental health prevention and management”; and the theme related to needs was “education and policies to promote mental health.” Considering the occupational and organizational characteristics of the police profession, individual and organizational interventions and policies are needed to adequately manage the mental health of police officers.